2017
DOI: 10.1007/s11064-016-2098-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neural Stem Cell and Olfactory Ensheathing Cell Co-transplants on Tissue Remodelling After Transient Focal Cerebral Ischemia in the Adult Rat

Abstract: Effects of neural stem cell and olfactory ensheathing cell cotransplants on tissue remodelling after transient focal cerebral ischemia in the adult rat. Neurochemical Research, 42(6), pp. 1599-1609.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/136264/ with the host-tissue post-transplantation is poor. In this study, we address this challenge by testing whether co-grafting of NSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Numerous experimental studies, including recent studies from our group, have demonstrated the potential of exogenously or endogenously derived stem cells alone or in combination with in situ tissue engineering strategies and/or pharmacotherapeutics in promoting transplant‐mediated repair with functional restoration through such diverse mechanisms as neuroprotection, cell replacement, remyelination, tissue/vascular remodelling and de novo neurogenesis (Augestad et al., ; Bible et al., ; Jendelová et al., ; Kokaia & Lindvall, ; Lindvall & Kokaia, ; Massensini et al., ; Medberry et al., ; Sandvig et al., ). Although highly promising and extremely valuable in elucidating relevant recovery mechanisms at the experimental level, clinical translation of such approaches tends to be confounded by significant challenges, such as allograft rejection as well as the intricacies inherent in trying to create safe, functional in situ biointerfaces that could effectively re‐establish functional connectivity in multiple foci (Sandvig et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental studies, including recent studies from our group, have demonstrated the potential of exogenously or endogenously derived stem cells alone or in combination with in situ tissue engineering strategies and/or pharmacotherapeutics in promoting transplant‐mediated repair with functional restoration through such diverse mechanisms as neuroprotection, cell replacement, remyelination, tissue/vascular remodelling and de novo neurogenesis (Augestad et al., ; Bible et al., ; Jendelová et al., ; Kokaia & Lindvall, ; Lindvall & Kokaia, ; Massensini et al., ; Medberry et al., ; Sandvig et al., ). Although highly promising and extremely valuable in elucidating relevant recovery mechanisms at the experimental level, clinical translation of such approaches tends to be confounded by significant challenges, such as allograft rejection as well as the intricacies inherent in trying to create safe, functional in situ biointerfaces that could effectively re‐establish functional connectivity in multiple foci (Sandvig et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, 80% stroke cases are ischemic stroke [15]. Ischemic events trigger complex molecular cascade reactions, including cell depolarization, excitotoxicity, impaired cellular energy metabolism, and disruption of the blood-brainbarrier [3]. Current treatments of ischemic stroke are limited to restore perfusion, promote circulation and protect cells from acute death [16].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cell transplantations have been showed of great therapeutic potential in neurorestoration. A number of studies have demonstrated that olfactory ensheathing cells (OECs) function in secretory [3,4], tissue remodeling [5], tissue migration [6][7][8] and immune regulation [8,9], and are prominent in repairing various nervous system diseases. In particular, OECs have eminent ability to stimulate axonal repair, enhance plasticity and support axonal retention in the central nervous system (CNS) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Reciprocally, NSC have been found as modulators of inflammation and tissue remodeling after several brain injuries, which might contribute to a feedback regulation loop in neurological diseases with neuroinflammatory component (Augestad et al, ). NSC may have a suppressive effect on inflammation via the inhibition of T‐cells (Einstein et al, ).…”
Section: Roles Of Hif In Stem Cellsmentioning
confidence: 99%